Dirty footprints and degenerate archives: Tabitha Nikolai's impure walking sims. Issue 1 (1st March 2020) - Gallagher, Rob
Tabitha Nikolai's Shrine Maidens of the Unseelie Court and Ineffable Glossolalia are impure specimens of the walking sim. While these are still first-person games that see players exploring eerily underpopulated environments and archiving textual fragments, they are at once more aesthetically reflexive and more referentially dense than many walking sims. Accommodating giant spiders, Weimar sexologists, messageboard trolls and quotations from Roman poetry, Nikolai's unorthodox spins on the 'archival adventure' reflect her interest in queer and trans history and her commitment to interrogating discourses of purity, progress and redemption. Reviewing critical discussions of the walking sim alongside queer, trans and decolonial perspectives on archives, identity and subjectification, the article argues that while walking sims have often been praised for telling emotionally engaging stories, in Nikolai's hands the form assumes different function: that of reckoning with history and exploring subjectivity.